Overexpression of vacuolar H+-pyrophosphatase from a recretohalophyte Reaumuria trigyna enhances vegetative growth and salt tolerance in transgenic Arabidopsis thaliana - Ningning Li; Yuzhu Cui; Zijian Zhang; Shuai Wang; Yaqing Sun; Shaoying Zhang; Guolong Li (Frontiers in Plant Science)
Reaumuria trigyna, a wild and endangered salt-secreting small shrub, is distributed in arid and semi-arid areas of Inner Mongolia, China. An H+-pyrophosphatase gene (RtVP1) was isolated from R. trigyna according to transcriptomic data, which encoded a plasma membrane and tonoplast-localized protein. RtVP1 was quickly upregulated by NaCl and exogenous abscisic acid treatment and rescued the sucrose deficiency sensitive phenotype of the AtVP1 mutant (avp1). Transgenic Arabidopsis overexpressing RtVP1 exhibited a higher leaf area, plant height, fresh weight, root length, and soluble carbohydrate accumulation compared to the wild type (WT) under normal conditions. RtVP1 overexpression increased the seed germination rate and decreased the reduction rate of fresh weight, root length, and chlorophyll content in transgenic plants under salt stress. Catalase enzyme activity, proline content, relative water content, and soluble sugar content were significantly increased in transgenic Arabidopsis under salt stresses, but the malondialdehyde content was dramatically decreased. More K+ and less Na+ were accumulated in transgenic Arabidopsis leaves, resulting in a relatively lower Na+/K+ ratio. In transgenic Arabidopsis roots, K+ was unchanged, but Na+ and the Na+/K+ ratios were reduced compared to those in WT. More Na+ and K+ were accumulated in the intracellular of transgenic yeast, and the Na+/K+ ratio was significantly reduced compared to the control. These results showed that R. trigyna RtVP1 promotes the vegetative growth of plants, mainly by regulating carbohydrate metabolism, and confers salt tolerance in transgenic Arabidopsis by maintaining Na+/K+ homeostasis and enhancing the antioxidant and osmotic regulatory capacity. These results indicated that RtVP1 can serve as an important candidate gene for genetic improvement of crop yield and salt tolerance.